IMPROVING SPEAKING ABILITY THROUGH TELLING PAST EXPERIENCE - Wiwik Yully Widyawati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
Abstract The study examines the teachers techniques in developing speaking ability, to identifies the difficulties faced by the students and, to finds out the teachers’ solution for the classroom problem in teaching and learning process in speaking. Design used is descriptive-qualitative study in describing the students’ ability to tell the past experience. To collect the data, the writer uses observation and interview and using a spoken test as the research instrument. Sample used is 38 students of Junior High School. The result of the research after being taught by using Telling past Experience is 76.42. Telling past experience was a bringing out a person’s individuality and personality at the past time. So, telling past experience can be used to give practice in speaking as well as in conducting this technique for teaching speaking. Yet student tend to get problems of being afraid of making mistakes and nervous. To overcome or to solve the problems making mistakes is a natural part of performing, convince to the students not to be scared of their audience, convince that the audience doesn’t know the students have made a mistake unless they tell them so and give them motivation not to give in to the fear. Key Word: Technique, Speaking Ability, Past Experience